2013
DOI: 10.1111/pan.12148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of topical tramadol and ketamine in pain treatment after tonsillectomy

Abstract: Topical tramadol and ketamine seem to be safe, effective, and easy analgesic approach for decreasing tonsillectomy pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 14 publications
(22 reference statements)
0
28
0
1
Order By: Relevance
“…Javid and colleagues [70] demonstrated that both subcutaneous and intravenous injections of ketamine at the end of surgery were safe and effective for post-tonsillectomy pain control without increasing the risk of complications. Two separate studies found the topical application of tramadol and ketamine to be a safe, effective, and easy analgesic approach for decreasing post-tonsillectomy pain [71,72] . Nielsen [73] suggested that a sufentanil and ketamine nasal spray provides a rapid onset of analgesia for a variety of painful procedures with few adverse effects and has promising features for use in pediatric procedural pain management.…”
Section: Pediatric Usementioning
confidence: 99%
“…Javid and colleagues [70] demonstrated that both subcutaneous and intravenous injections of ketamine at the end of surgery were safe and effective for post-tonsillectomy pain control without increasing the risk of complications. Two separate studies found the topical application of tramadol and ketamine to be a safe, effective, and easy analgesic approach for decreasing post-tonsillectomy pain [71,72] . Nielsen [73] suggested that a sufentanil and ketamine nasal spray provides a rapid onset of analgesia for a variety of painful procedures with few adverse effects and has promising features for use in pediatric procedural pain management.…”
Section: Pediatric Usementioning
confidence: 99%
“…Other studies used ketamine topically after tonsillectomy; the treatment produced an analgesic effect and decreased the need for rescue medication. [14][15][16] Satilmiş et al 12 investigated the efficacy of adding ketamine to local anesthetic agents to increase the duration of regional anesthesia and postoperative analgesia during surgical extraction of third molars. They concluded that the combination of a local anesthetic and sub-anesthetic doses of ketamine can produce good local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes analyzed were postoperative pain (pain scores after leaving the operation room) [2][5], [8][23], postoperative (24 hours) analgesic requirements (either doses or percentage of patient receiving postoperative opioids or nonopioids analgesics)[2][4], [8][10], [12][14], [16], [19], [20], [22][25], time to first analgesic administration (opioid or nonopioid analgesics administered with a defined pain intensity target)[3]–[5], [8][10], [12][14], [18], [22], [23], [26], time to first oral uptake [2], [5], [13], [14], postoperative nausea and vomiting (percentage of patients or dose of antiemetics) [2], [8], [9], [12]–[18], [24], [25] and the occurrence of psycho-mimetic manifestations including nightmares [9], [10], [18], sleep pattern change (percentage of patients) [9], [10], [12], [19], hallucinations (percentage of patients) [5], [8], [18], [19], [25] or sedation (sedation scores) [4], [5], [8], [9], [11], [15], [17], [24]. These outcomes were compared with preoperative ketamine ...…”
Section: Methodsmentioning
confidence: 99%